Short- and Long-Term Variations in the Reykjanes Geothermal Reservoir From Seismic Noise Interferometry - Sánchez-Pastor, Pilar (author); Obermann, Anne (author); Schimmel, Martin (author); Weemstra, C. (author); Verdel, Arie (author); Jousset, Philippe (author) (Geophysical Research Letters, 2019)
The Reykjanes Geothermal System (RGS) is a high-temperature geothermal system located on the Reykjanes peninsula, a transtensional plate-boundary zone located on the southwestern tip of Iceland. The area is characterized by high seismicity, recent volcanism, and high-temperature geothermal fields. We use seismic noise records from April 2014 to August 2015 to study stress changes and potential deformation of the subsurface caused by injection and production operations at RGS through seismic interferometry. We retrieve continuous time series of waveform similarity values and seismic velocity changes during this period. The S-transform of the similarity values allows us to clearly identify three variations in the mechanical properties of the Reykjanes peninsula related to rapid changes of RGS production. In addition, we observe a slow seismic velocity decrease of 0.36%/year in the reservoir due to the water deficit and seasonal variations associated with the energy production demand. Applied Geophysics and Petrophysics